Highly Efficient Bilayer Polymer Solar Cells Using the Method of Sequential Processing with Additive Bilayer - Lee, Jihoon; Jang, Soyeong; Tamilavan, Vellaiappillai; Li, Ning; Wang, Rong; Lüer, Larry; Lee, Dalyong; Yoon, Jung Won; Lee, Bo Ram; Choi, Hyosung; Park, Sung Heum; Brabec, Christoph (Solar RRL, 2023)
Despite the research value of bilayer organic solar cells (OSCs) for commercialization in the future, the bulk-heterojunction (BHJ) structure dominates the fabrication of OSCs because of its higher power conversion efficiency (PCE) compared with bilayer OSCs. Herein, four different types of bilayer OSC structures using sequential processing (SP) with an additive bilayer are investigated and considerably enhanced device performance is demonstrated. The performance of our bilayer devices based on a wide bandgap (PBDT-DPPD-TPD; P2) polymer and [6,6]-phenyl C61-butyric acid methyl ester (PCBM) is improved from 2.88% for the conventional bilayer structure to 6.62%. More importantly, remarkable PCEs of 8.78% and 15.16% for PTB7-Th/PCBM and PM6/Y6 bilayer OSCs, respectively, using the SP with additive bilayer method are achieved and the inhomogeneity issues of the BHJ structure are successfully addressed. Herein, a novel way to overcome the low efficiency of bilayer OSCs is suggested and an unprecedented possibility of renovation, breaking the standardization of OSC research, is presented.
CRIS-Team Scopus Importer:2023-01-20
Keywords: bilayer structures; high efficiency; organic solar modules; polymer solar cells; processing additives